Developing of Articulate Storyline of Economic Learning Media to Improve Student Learning Outcomes at SMA Negeri 1 Deli Tua - Marito Ritonga; Indra Maipita; Khairuddin E. Tambunan (Universitas Pancasakti Tegal, 2022)
This study aimed to develop and implement Articulate Storyline economic learning media to improve economic learning outcomes for class XI students of SMA Negeri 1 Deli Tua. This research is development research (R&D) with the ADDIE method. This research was conducted at SMA Negeri 1 Deli Tua, with a population of all students of class XI IPS. The results of this study are based on the assessment carried out by validation experts and user responses, the average percentage of assessment is 92%